Ethics For Using Slang In Teenager Communication On Social Media - Alya Marsya Naumi; Maya Sulis Tiani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to investigate the ethics of using slang language in adolescent communication on social media. The research method employed is qualitative analysis of content generated by adolescents on popular social media platforms. Findings reveal that the use of slang language significantly impacts adolescents' perceptions, identities, and social relationships. The implications underscore the need for a more discerning approach to slang language use on social media to promote awareness of communication ethics.